1987
DOI: 10.1002/actp.1987.010381105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of degradative treatments on cotton graft copolymers. Part III. Oxidation of poly(methacrylic acid)‐cotton graft copolymers by sodium hypochlorite

Abstract: Hypochlorite oxidation of poly(methacry1ic acid)-cotton graft copolymers was examined and compared with that of ungrafted and initiator-treated cottons. The extent and rate of oxidation, carboxyl content, copper number, and tensile strength were measured in dependence of time. The results are discussed with respect t o the structure of the original and the grafted cotton. Der EinfluP oon Abbaubehandlungen auf Baumwoll-Pfropfcopolymere. Teil I I I . Oxidation von Poly(methacry1sciure)-Baumwoll-Pfropfcopolymeren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Thus, the higher availability of monomer radical sites in the vicinity of immobile cellulose macroradical increased the percent graft yield. 5,23 From our experiment, it was observed that the percent graft efficiency decreased with the increase of monomer concentration, as more monomer radical prevails to form homopolymer over grafting.…”
Section: Effect Of Variation Of Monomer Concentrationmentioning
confidence: 91%
“…Thus, the higher availability of monomer radical sites in the vicinity of immobile cellulose macroradical increased the percent graft yield. 5,23 From our experiment, it was observed that the percent graft efficiency decreased with the increase of monomer concentration, as more monomer radical prevails to form homopolymer over grafting.…”
Section: Effect Of Variation Of Monomer Concentrationmentioning
confidence: 91%
“…This is because in the absence of KMnO 4 in the polymerization medium, cellulose as well as monomer were not converted to their radicals. 23 However, the percent graft yield increased with the increase of permanganate concentration up to 0.6%-0.9%-that is 0.6% for AN and 0.9% for MAN and beyond this range, the graft yield decreased. A similar behavior also was true for homopolymer.…”
Section: Effect Of Initiatormentioning
confidence: 94%
“…This may be because of the higher availability of monomer molecules in the vicinity of immobile cellulose macroradicals as well as a higher monomer concentration in the polymerization medium. The greater availability of the monomer in the polymerization medium acted in favor of molecular collision, 5,23 thereby enhancing polymerization in general or homopolymer formation in particular. The decreased percent graft yield of more than 80% suggests that homopolymerization prevails over grafting at a higher monomer concentration.…”
Section: Effect Of Monomermentioning
confidence: 98%
“…In addition, the Br 2 molecules liberated at higher bromate concentrations [Eq. (7)] may also contribute to the oxidation of chitosan with subsequent degradation of the chitosan macromolecules [17][18][19][20][21][22] .…”
Section: Chitosan Graft Copolymers 431mentioning
confidence: 99%